Asociación entre el consumo de alcohol y/o drogas y el uso del preservativo en adolescentes escolarizados en los Estados Unidos durante el 2017 - Calero Romero, María José (2020)
The consumption of alcohol and drugs of abuse are a more common cause of risky sexual behavior in young people that can lead to serious consequences. Many studies have evaluated the association between alcohol or drugs as different exposure factors in different scenarios and in a period of time leaving a doubt as to whether there was consumption of any other substance not included in the measurement of the exposed variables or if the consumption was before , during or after sexual intercourse. In this work it is expected to study both, alcohol and drugs of abuse as a single priority factor of exposure during a single sexual relationship and if the condom was used in that specific sexual encounter. Consequently, it will be determined whether the use of these substances is associated with the concurrent use of condoms. In this way, prevention strategies will be a primary care plan and will be a primary health care plan in order to avoid harmful consequences for adolescents.